The effect of intensity soccer training sessions on marked biochemical indicators of blood acidity of saudi young soccer players - Alshuwaier, G. O.; Ghazzawi, H. A.; Alaqil, A. I.; Alsharif, Y.R.; Alibrahim, M. S.; Aljaloud, K. S. (Open Access Journal of Sports Medicine, 2022)
Purpose To assess the effect of low-to-moderate-intensity exercise on specific blood biomarkers and blood acidity in young Saudi Arabian professional soccer players.